2023
DOI: 10.1097/pxr.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

What is the cost, impact, and willingness to pay for an Amputee Peer Support Program?

Abstract: Background:The provision of peer support from those who have already made positive adjustments to amputation is recommended for people incurring a major limb amputation; however, few receive this service.Objective:From a program perspective, determine the cost, impact, and willingness to pay for an Amputee Peer Support Program.Study design:Cost analysis.Methods:Cost of the Amputee Peer Support Program included a cost analysis of program data over a 5-year time horizon (2013–2018) reported in Australian Dollars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Four of the studies reported on the perceived benefit that peer support had an impact on self-management and well-being. 27 , 30 , 32 , 37 Participants reported that this type of social support boosted their self-esteem, confidence, 27 , 32 , 37 and self-efficacy. 30 In addition, this type of support group led to increased autonomy and well-being.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the studies reported on the perceived benefit that peer support had an impact on self-management and well-being. 27 , 30 , 32 , 37 Participants reported that this type of social support boosted their self-esteem, confidence, 27 , 32 , 37 and self-efficacy. 30 In addition, this type of support group led to increased autonomy and well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of these studies described programs implemented in community settings, including charities, organizations, and clinics. 21 , 22 , 24 , 27 30 Four studies described programs facilitated in rehabilitation settings. 25 , 31 - 33 While one study discussed peer support being implemented within a hospital and community setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation